2011
DOI: 10.1021/om1005512
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanism of R−R Reductive Elimination from the Six-Coordinate d6 Complexes L2Pt(R)4 (R = vinyl, Me)

Abstract: We have used density functional theory to investigate the reductive elimination from platinum(IV) structures of the form L 2 PtR 4 where L=PMe 3 , PH 3 , PF 3 , CO, NH 3 and R=vinyl, Me. We conclude that reductive elimination occurs via the L-predissociation pathway for R=Me, irrespective of ligand L. But when R=vinyl, direct elimination is the preferred pathway if the L ligand is PMe 3 ; otherwise both pathways are competitive for R=vinyl. We also note that if L is more π-electron accepting and less σ-electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 88 publications
1
18
0
Order By: Relevance
“…A theoretical investigation carried out by Morokuma and co‐workers on the vinyl–vinyl reductive elimination from bis‐σ‐vinyl complexes [(PH 3 ) 2 Pt(vinyl) 2 X 2 ] (X=Cl, Br, I) suggested that C(sp 2 )−C(sp 2 ) reductive elimination occurs directly from six‐coordinate Pt IV complexes . Detailed computational investigations by Yates and co‐workers showed that although the ligand pre‐dissociation pathway is favorable for the case R=Me, direct elimination is preferred for the system R=vinyl during reductive elimination from [L 2 Pt(R) 4 ] (R=Me, vinyl; L=PMe 3 , PH 3 ) complexes . The above findings prompted us to consider two possible reaction channels for the reductive elimination event emanating from six‐coordinate Pd IV intermediate 7 A (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…A theoretical investigation carried out by Morokuma and co‐workers on the vinyl–vinyl reductive elimination from bis‐σ‐vinyl complexes [(PH 3 ) 2 Pt(vinyl) 2 X 2 ] (X=Cl, Br, I) suggested that C(sp 2 )−C(sp 2 ) reductive elimination occurs directly from six‐coordinate Pt IV complexes . Detailed computational investigations by Yates and co‐workers showed that although the ligand pre‐dissociation pathway is favorable for the case R=Me, direct elimination is preferred for the system R=vinyl during reductive elimination from [L 2 Pt(R) 4 ] (R=Me, vinyl; L=PMe 3 , PH 3 ) complexes . The above findings prompted us to consider two possible reaction channels for the reductive elimination event emanating from six‐coordinate Pd IV intermediate 7 A (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of each of the complexes 1 with iodobenzenedichloride is rapid, taking place in less than one minute, even at temperatures as low as -60 °C. 2.2294 (8); C(1)-C(6) 1.424(4); C(6)-C(7) 1.464(5); N(7)-C(11) 1.350(4); N(7)-C(7) 1.360(4); C(11)-C(12) 1.474(4); C(12)-C(17) 1.420(4); N(7)-Pt(1)-C(1); 80.40 (12); N(7)-Pt(1)-C(17) 79.90 (11); C(1)-Pt(1)-C(17) 159.24 (12); N(7)-Pt(1)-P(1) 178.57(7); C(1)-Pt(1)-P(1) 99.71 (9); C(17)-Pt(1)-P(1) 100.15(9); C(6)-C(1)-Pt(1) 111.9(2); C(11)-N(7)-C(7) 123.6(3). [11][12] This process takes place via a two step mechanism: the initial delivery of a Cl + to give a five-coordinate complex, with subsequent addition of a sixth ligand (normally Cl -).…”
Section: Resultsmentioning
confidence: 99%
“…101.19(19); C100-Pt1-C17 98.7(2); C100-Pt1-P1 86.93(18); I2-Pt1-I1 87.08(7); C1-Pt1-I1 87.67 (11); C1-Pt1-I2 101.38 (12); C1-Pt1-P1 94.30 (11); N7-Pt1-I1 88.61(9); N7-Pt1-C100 175.85(19); N7-Pt1-I2…”
Section: Figurementioning
confidence: 99%